Predicting the risk of type 2 diabetes through anthropometric indices in Pakistani adults- A sub-analysis of second National diabetes survey of Pakistan 2016–2017 (NDSP-07). Issue 2 (March 2021) - Basit, Abdul; Mustafa, Nida; Waris, Nazish; Askari, Saima; Fawwad, Asher; ,; Rehman Abro, Mujeeb Ur; Ishfaq Ahmed, Khawaja; Ahmed, Khurshid; Sabir Ali, Sobia; Bilal, Ahmed; Butt, Anam; et al.
Abstract: Background and aim: Excess adiposity is associated with an increased risk of diabetes. Amongst the various measures of adiposity, the most appropriate one to predict the risk of diabetes remains debatable. Therefore, the aim of this study was to compare the ability of body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) in predicting type 2 diabetes mellitus (DM) among Pakistani adults. Subjects and methods: This was the sub-analysis of a large population based Second National Diabetes Survey of Pakistan (NDSP) 2016–2017. With this survey, 10834 individuals were recruited and 4788 individuals fulfilled the inclusion criteria for this sub-analysis (subjects with missing anthropometric details were excluded). Participants were categorized into two groups; subjects with type 2 DM and subjects without DM. Data of participants was collected via pre-designed detailed questionnaire. Clinical and anthropometric measurements were measured using standardized techniques. Results: Out of 4788 individuals, 3085(64.4%) were non-DM subjects and 1703(35.6%) were type 2 DM subjects with mean age of 39.78 ± 13.79 and 50.38 ± 11.33 years, respectively. Logistic regression analysis revealed a significant association of WC with type 2 diabetes after adjustment for possible confounders. Area under the curve (AUC) of WC was found higher than AUC of BMI and WHR. Conclusion: The findings from second NDSP (2016–2017) demonstrated that WC is a better marker than WHR and BMI in predicting type 2 DM for Pakistani population. Highlights: Several anthropometric indices have been used for predicting diabetes. The results of studies regarding superiority of these indices are inconsistent. Body mass index, waist circumference and waist to hip ratio are significant predictors of type 2 diabetes. Waist circumference is the best adiposity measurement in predicting type 2 diabetes among Pakistani adults.